2010
DOI: 10.1073/pnas.1004269107
|View full text |Cite
|
Sign up to set email alerts
|

Ordering dynamics of blue phases entails kinetic stabilization of amorphous networks

Abstract: The cubic blue phases of liquid crystals are fascinating and technologically promising examples of hierarchically structured soft materials, comprising ordered networks of defect lines (disclinations) within a liquid crystalline matrix. We present large-scale simulations of their domain growth, starting from a blue phase nucleus within a supercooled isotropic or cholesteric background. The nucleated phase is thermodynamically stable; one expects its slow orderly growth, creating a bulk cubic phase. Instead, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…As mentioned earlier, Henrich et al (31) have shown that, during homogeneous nucleation, the formation of BPI starting from Chol, and the formation of BPII starting from Iso appear to follow a sequence of metastable states. In our calculations and experiments, the system is confined and the patterned surfaces act as the preferred nucleation site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, Henrich et al (31) have shown that, during homogeneous nucleation, the formation of BPI starting from Chol, and the formation of BPII starting from Iso appear to follow a sequence of metastable states. In our calculations and experiments, the system is confined and the patterned surfaces act as the preferred nucleation site.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these authors simulated BPI or BPII nuclei embedded in an isotropic or a cholesteric background (31), and found that BPs grow disorderly from the nuclei, leading to metastable states characterized by an amorphous defect network. In their work, the nuclei were quenched to temperatures where the BPI and BPII are thought to be stable; these authors then suggested that the ordering dynamics of BPs exhibits a hierarchical nature, which requires a secondary nucleation stage to control the nucleation and orientation of bulk BPs.…”
Section: Significancementioning
confidence: 99%
“…In addition, it is a priori uncertain that a BP nucleating from an isotropic phase dispersed with colloids will form the same cubic lattices that it does in the absence of particles. Thus, there is ample motivation for studying the kinetic aspects of colloidal particles in BPs, addressing domain growth (45), possible thermal annealing, and external fields assisted assembly.…”
Section: Discussionmentioning
confidence: 99%
“…We employ a 3D hybrid lattice Boltzmann (LB) algorithm [15,[17][18][19] to solve the Beris-Edwards equations. The evolution of the Q tensor [20] is…”
mentioning
confidence: 99%